Dictionary of marketing terms - Bennett, Peter D.; American Marketing Association (Lincolnwood, Ill., USA : NTC Business Books, 1995)
Reference guide for professionals and students with more than 2,500 definitions of terms from various aspects of the marketing field, including day-to-day and specialized vocabulary.
Includes bibliographical references (p. 309-316).
Booklist.
Choice.
Adult
Keywords: Marketing -- Dictionaries; Marketing -- Dictionaries